A pilot observational study on magnesium and calcium imbalance in elderly patients with acute aortic dissection. Issue 1 (December 2017) - Vianello, E.; Dozio, E.; Barassi, A.; Sammarco, G.; Tacchini, L.; Marrocco-Trischitta, M.; Trimarchi, S.; Corsi Romanelli, M.
Abstract Background Magnesium (Mg) and calcium (Ca) are the principal essential elements involved in endothelial cell homeostasis. Extracellular changes in the levels of either alter endothelial contraction and dilatation. Consequently Mg and Ca imbalance is associated with a high risk of endothelial dysfunction, the main process observed during acute aortic dissection (AAD); in this clinical condition, which mainly affects elderly men, smooth muscle cell alterations lead to intimal tears, creating a false newlumen in themedia of the aorta. AAD patients have a high risk of mortality as a result of late diagnosis because often it is not distinguished from other cardiovascular diseases. We investigated Mg and Ca total circulating levels and the associated pro-inflammatory mediators in elderly AAD patients, to gain further information on the pathophysiology of this disorder, with a view to suggesting newer and earlier potential biomarkers of AAD. Results Total circulating Mg and Ca levels were both lower in AAD patients than controls (p  < 0.0001). Using Ca as cut-off, 90% of AAD patients with low Ca (<8.4 mg/dL) came into the type A classification of AAD. Stratifying AAD according to this cut-off, Mg was lower in patients with lower total Ca. Compared to controls, both type A and B AAD patients had higher levels of all the pro-coagulant and pro-inflammatory mediators analyzed, including sP-sel, D-dimer, TNF-α, IL-6, and CRP (p  < 0.05). Dividing types A and B using the Stanford classification, no significant differences were found (p  > 0.05) The levels of both ICAM-1 and EN-1 were lower in AAD than in a control group (p  < 0.0001 andp  < 0.05 respectively). Conclusions These findings suggest that low Mg and Ca in AAD elderly patients may contribute to altering normal endothelial physiology and also concur in changing the normal concentrations of different mediators involved in vasodilatation and constriction, associated with AAD onset and severity.